Question Number 194219 by Shlock last updated on 30/Jun/23 | ||
![]() | ||
Answered by Frix last updated on 30/Jun/23 | ||
![]() | ||
$$\left({x}^{\mathrm{3}} +\mathrm{4}{x}−\mathrm{8}\right)\left({x}^{\mathrm{3}} −\mathrm{2}{x}^{\mathrm{2}} +\mathrm{8}\right)\left({x}+\mathrm{2}\right)= \\ $$$$={x}^{\mathrm{7}} +\mathrm{64}{x}^{\mathrm{2}} −\mathrm{128} \\ $$$${x}^{\mathrm{3}} +\mathrm{4}{x}−\mathrm{8}=\mathrm{0}\:\Rightarrow \\ $$$${x}^{\mathrm{7}} +\mathrm{64}{x}^{\mathrm{2}} −\mathrm{128}=\mathrm{0}\:\Leftrightarrow\:{x}^{\mathrm{7}} +\mathrm{64}{x}^{\mathrm{2}} =\mathrm{128} \\ $$ | ||
Commented by Shlock last updated on 30/Jun/23 | ||
Thanks, sir! | ||